2018
DOI: 10.1097/mph.0000000000001295
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Folic Acid and Homocysteine in Thalassemia Major Patients Before and After Folic Acid Supplement Cessation

Abstract: Cessation of folic acid supplementations in beta thalassemia major patients can lead to a significant decrease in serum folic acid and increase in Hcy levels. According to our findings and efficacy of folic acid in patients with beta thalassemia major, it is recommended to use the supplementation in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…19 No changes in erythrocyte parameters were observed. Of interest, Baghersalimi et al 34 reported that in Thal patients taking clinically prescribed folate supplements (1 mg/d) for a minimum of 6 months, cessation of supplement use led to significantly increased serum homocysteine, and decreased serum folic acid.…”
Section: Folatementioning
confidence: 99%
“…19 No changes in erythrocyte parameters were observed. Of interest, Baghersalimi et al 34 reported that in Thal patients taking clinically prescribed folate supplements (1 mg/d) for a minimum of 6 months, cessation of supplement use led to significantly increased serum homocysteine, and decreased serum folic acid.…”
Section: Folatementioning
confidence: 99%
“…Iron chelation therapy, which is used in β-TM to reduce IO, is widely used to prevent the consequences of IO on heart, liver, bones, and immune system [21] but is usually associated with many adverse effects including infections [9,22]. Some clinicians propose that treatment with vitamin C and folic acid in TM patients may improve erythropoiesis and the secondary deficiencies in these vitamins [23,24]. The iron status in β-TM patients undergoing blood transfusions can be monitored by noninvasive methods including measurements of serum iron (Fe), which is distributed within the body via plasma transferrin (Tf), a transport protein that mediates iron exchange between tissues, total iron-binding capacity (TIBC), Tf levels, Tf saturation percentage (TS%), unsaturated iron-binding capacity (UIBC) and ferritin levels [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the first reaction, Hcy is converted to methionine by using cobalamin as cofactor. Cobalamin deficiency results in the accumulation of Hcy that induce lipid peroxidation and generate free radicals, resulting in endothelial dysfunction 2,3. Hyperhomocysteinemia and low vitamin B 12 concentration play an essential role in endothelial damage and are independent risk factors for CVD in adult patients with coronary artery disease 4.…”
mentioning
confidence: 99%
“…Cobalamin deficiency results in the accumulation of Hcy that induce lipid peroxidation and generate free radicals, resulting in endothelial dysfunction. 2,3 Hyperhomocysteinemia and low vitamin B 12 concentration play an essential role in endothelial damage and are independent risk factors for CVD in adult patients with coronary artery disease. 4 Also, severe acquired vitamin B 12 deficiency could lead to a condition that mimics thrombotic microangiopathies.…”
mentioning
confidence: 99%